2021
DOI: 10.4236/ojst.2021.119033
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Floor Fractures: Epidemiological, Clinical and Therapeutical Study at Sylvanus Olympio University Teaching Hospital in Lomé about 51 Cases

Abstract: Introduction: Orbital floor fractures are a significant pathology among maxillofacial injuries. They can cause oculomotor, sensory, and sometimes esthetic disorders. The goal of this study was to determine the epidemiological profile of orbital floor fractures and show their clinical and therapeutic approach in Lomé. Patients and method: This was a descriptive retrospective study of orbital floor fractures collected in the ENT and maxillofacial surgery department of Sylvanus Olympio University Hospital in Lomé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In studies conducted in developing regions such as India, road traffic accidents (74.7-92.16%) were reported more frequently as the most common etiology in MFTs [29,[37][38][39]. In our study, road traffic accidents (25.5%) were the second most common etiology in MFTs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In studies conducted in developing regions such as India, road traffic accidents (74.7-92.16%) were reported more frequently as the most common etiology in MFTs [29,[37][38][39]. In our study, road traffic accidents (25.5%) were the second most common etiology in MFTs.…”
Section: Discussionsupporting
confidence: 55%
“…Among the causes of road traffic accidents in developing countries, reasons such as poorly defined traffic rules, inadequate traffic lighting, inadequacy of signage, and uncontrolled vehicles have been reported [30,[37][38][39][40][41]. However, with the increasing population density in some developed countries, it has been reported that MFTs, due to road traffic accidents caused by drivers, driving at an earlier age, increasing carelessness and non-compliance with traffic rules [23,28,29,38,42].…”
Section: Discussionmentioning
confidence: 99%